Love and Marital Quality in Romantic Relationships Mediated and Non-Mediated by Internet - Haack, Karla Rafaela; Falcke, Denise (Paidéia (Ribeirão Preto), 2014)
Love is one of the most desired feelings by human beings. According to the triangular theory of love, it is composed of three elements: intimacy, passion and decision/commitment, which constitutes a dimension related to the quality of love the partners perceive in their relationship. This study aims to compare the three elements of love and marital quality of 86 Internet users (43 in a relationship mediated by the Internet and 43 with a physical relationship). The results indicate that there is a significant difference in the intimacy, the decision/commitment and the whole dimension of love, as well as in the marital quality between partners who have a relationship mediated by Internet and the ones in a physical relationship. We can conclude that the Internet is a great tool for people to meet, but that it is important for the relationship to develop in a face-to-face context.